Perancangan Dan Pengembangan Strategı Promosı Vıdeo Destınası Wısata Kota Batam - Zulkarnain Zulkarnain; Welvin Hendrison (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
The purpose of this practical work is to help OMA Tour & Travel in promoting several tourist destinations in Batam City to local and foreign tourists by using videos as promotional media that will be published on Youtube. This video contains several collections of information about tourist attractions such as place descriptions, available facilities, entrance ticket prices, operational times, as well as addresses and locations of tourist attractions. In the process of merging videos, the author will use the Wondershare Filmora X application as a means to combine the videos. Data collection techniques carried out in this activity are observation, interviews, and also documentation. The author hopes to help increase local and foreign tourist customers and expand marketing reach on OMA Tour & Travel.